The Role of Performance Appraisal and Punishment Systems in Enhancing Hotel Employee Performance in Semarang Region - Muhammad Aji Pamungkas; Krisnawati Setyaningrum Nugraheni (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to analyze the effect of performance appraisal and punishment on employee performance in starred hotels in Semarang, Indonesia. In the hospitality industry, where service quality heavily depends on human capital, performance evaluation and behavioral control systems play a critical role in sustaining productivity. This research employs a quantitative approach with a survey method involving 70 respondents from three- to five-star hotels. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The results indicate that both performance appraisal and punishment significantly influence employee performance, both partially and simultaneously. Performance appraisal demonstrates a more dominant effect than punishment in enhancing motivation and work productivity. The effectiveness of these systems is influenced by consistent implementation, open communication between management and employees, and alignment with organizational goals. This study offers practical recommendations for hotel managers in designing fair and effective performance management systems. Theoretically, it contributes to the human resource management literature in the service sector, particularly in hospitality management.